The Implementation of Online Learning Based Schoology Application to Improve Students’ Abilities to Express Opinions - Dilla Octavianingrum (Teknodika, 2021)
This research aims to describe online learning implementation based on the schoology application in improving students’ opinion skills. This study's subjects were 40 students of the performing arts education study program, isi yogyakarta, who attended the lesson planning course in the 2019/2020 academic year. This research employed classroom action research (car). The research stages comprised planning the action, implementing the action, observing and interpreting it, and analyzing and reflecting. The results showed that schoology-based online learning could improve students’ opinion skills because they could express their opinions in writing. Besides, the use of schoology was considered interesting and useful for online learning. An increase in students' ability to express their opinions was revealed during the implementation of schoology-based online learning. This increase was marked by the percentage of students’ abilities to express opinions in the lesson planning course, namely 26% (cycle i 62%, cycle ii 88%).